Estudo de deformabilidade e empacotamento de britas com diferentes origens litológicas do estado do Rio Grande do Sul - Sagrilo, Amanda Vielmo (2020)
This research aimed to evaluate the unbounded graded granular materials behavior towards resilient and permanent deformation, employed as pavements base course from different aggregates in Rio Grande do Sul. The studied lithologies were São Juvenal basalt, Della Pasqua rhyodacite and SBS Engenharia syenogranite. Material was collected from road jobsites (curves CA, 509 and KM3) and were adjusted to a single grain size distribution (SJ Ajuste, DPA Ajuste and SBS Ajuste). The preliminary tests carried out were sieve analysis, absorption curve and compaction tests. For jobsite curves, RM tests were performed, while for adjusted curves, RM, PD, x-ray tomography and mechanistic analysis by MeDiNa. The compaction energy is modified and the equipment used in RM and PD is the repeated loading triaxial (RLT). The absorption tests, according to the granulometric fraction justified the high optimum moisture content (OMC) reached by the rhydacite, which presents high absorption. The resilient modulus test performed followed the compaction curve trend, so higher dry densities returned greater resilient modulus. This trend was followed also by the x-ray tomography, which the lower void volume presented greater resilient modulus. For permanent deformation tests, the obtained results were more related to mechanical properties of the rock, since as the syenogranite, among the analyzed rocks, is the most susceptible to crushing and abrasion, showing the less desirable performance. For shakedown analysis, the graphic methodologies of Dawson and Wellner (1999), Werkmeister (2003), Gu et al (2017) and Alnedawi et al (2019) were used. The PD tests whose ratio (⁄3) is equal to 1, presented or, with more cycles, would present accommodation, while the others had B or C behavior. The RM test after the PD test showed to be an important shakedown indicator, in which the resilient behavior of the material helps to determine if the sample is accommodating, in relation to the traditional RM test. Then, the mechanictic analysis demonstrated the employability of the material, the permanent deformation (mm) and cracked area (%) of the proposed typical structure and the feasibility of the studied materials